Beginning design for 3D printing - Micallef, Joe (Technology in action series., 2015)
Beginning Design for 3D Printing is the full color go-to-guide for creating just about anything on a 3D printer. This book will demystify the design process for 3D printing, providing the proper workflows for those new to 3D printing, eager artists, seasoned engineers, 3D printing entrepreneurs, and first-time owners of 3D printers to ensure original ideas can be 3D printed. Beginning Design for 3D Printing explores a variety of 3D printing projects. Focus is on the use of freely available 3D design applications with step-by-step techniques that will demonstrate how to create a wide variety of 3D printable objects and illustrate the differences between splines, polygons, and solids. Users will get a deep understanding of a wide range modeling applications. They'll learn the differences between organic modeling tools, hard edge modeling, and precision, CAD-based techniques used to make 3D printable designs, practical products, and personalized works of art. Whether you are a student on a budget or a company exploring R & D options for 3D printing, Beginning Design for 3D Printing will provide the right tools and techniques to ensure 3D printing success.